Correction of Deep Overbite by Using a Modified Nance Appliance in an Adult Class II Division 2 Patient with Dehiscence Defect. (6th September 2018) - Li, Zhujun; Chen, Zhengxi; Sun, Jian; Yang, Li'an; Chen, Zhenqi
Abstract : A modified Nance Appliance (MNA) is introduced as a treatment option for an adult class II division 2 malocclusion (CII/2) patient with deep overbite and dehiscence on the facial root surface of retroclined upper incisors through the cone-beam computed tomography (CBCT). Indications for this modified MNA as well as a brief description of fabrication procedure and biomechanical analysis of the treatment effects are shown in detail. Root control and absolute intrusion without enlarging the bony defect were achieved. The treatment results were satisfying and favorable.